2006
DOI: 10.1038/modpathol.3800493
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and non-AIDS diffuse large B-cell lymphomas express different antigen profiles

Abstract: Based on gene expression profiling, diffuse large B-cell lymphomas arising in immunocompetent patients can be divided into germinal center and activated B-cell types. Since little is known about acquired immunodeficiency syndrome associated diffuse large B-cell lymphomas, we tested whether the protein expression of germinal center and activated B-cell markers differed between acquired immunodeficiency syndrome (AIDS) vs non-AIDS diffuse large B-cell lymphomas. We immunohistochemically stained tissue microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
5
22
2
Order By: Relevance
“…Previous studies have described high rates of co-expression of GC antigens and activation markers in HIV associated lymphomas. 6,8 This might represent a final stage of intra-GC differentiation in ARL, suggesting a unique pathophysiology. Our results are in line with this observation and show CD10 and MUM-1 co-expression more prevalent than in HIV-negative series (12% x 1%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described high rates of co-expression of GC antigens and activation markers in HIV associated lymphomas. 6,8 This might represent a final stage of intra-GC differentiation in ARL, suggesting a unique pathophysiology. Our results are in line with this observation and show CD10 and MUM-1 co-expression more prevalent than in HIV-negative series (12% x 1%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the rate of nongerminal center B-cell-like lymphoma among the remainder is 88% (23/26), similar to our rate. Recently, Madan et al 48 performed hierarchical cluster analysis using scores of immunohistochemical stains for germinal center differentiation and activated B-cell markers on diffuse large B-cell lymphoma from two groups of patients, one with positive and the other with negative HIV status. They concluded, despite the overlap in their clusters, that diffuse large B-cell lymphomas have different immunophenotypes in patients with the acquired immunodeficiency syndrome (AIDS) compared to those without.…”
Section: Discussionmentioning
confidence: 99%
“…53 The common morphologic variants of DLBCL include centroblastic, immunoblastic and anaplastic variants. Chang et al, 59 Madan et al 60 found that the immunophenotype in AIDS-related It is noteworthy that in one of few studies to emerge from Africa, specifically Uganda, Tumwine et al 62 established that the activated germinal center-type DLBCL, defined as those expressing CD10, Bcl-6, MUM1 and CD138, was found to have the best prognosis relative to other groups of DLBCL in their study.…”
Section: Morphologic Subtypes Of Dlbclmentioning
confidence: 99%